New Safety Paradigm: Management and Occupational Health and Safety (OHS) Synergy in the Digital Era. - Andika Prasetya Nugraha, Andika; Irawati, Ice; Nabella, Septa Diana; Mulyadi, Mulyadi; Nurmayunita, Nurmayunita (Postgraduate Management Journal, 2024)
This study explores the synergy between management Occupational Health and Safety (OHS) as the key to success in creating a safe, productive, and sustainable work environment in the modern era. In the face of technological challenges and the complexity of the work environment, the integration of OHS principles into a company's management strategy is crucial. Although many organizations have implemented OHS programs, they are often seen as a separate function, resulting in high rates of occupational accidents and illnesses. This study identifies effective strategies to synergize management and OHS, including the use of modern technology and the development of a comprehensive safety culture. Thus, this research provides valuable insights in improving occupational safety, operational efficiency, and business sustainability in the digital era.